Magnetic Resonance Assessment of Left Ventricular Ejection Fraction at Any Time Post‐Infarction for Prediction of Subsequent Events in a Large Multicenter STEMI Registry. Issue 2 (16th June 2021) - Gavara, Jose; Marcos‐Garces, Victor; Lopez‐Lereu, Maria P.; Monmeneu, Jose V.; Rios‐Navarro, Cesar; de Dios, Elena; Perez, Nerea; Merenciano, Hector; Gabaldon, Ana; Cànoves, Joaquim; Racugno, Paolo; Bonanad, Clara; et al.
Abstract : Background: Magnetic resonance imaging (MRI) is the most accurate imaging technique for left ventricular ejection fraction (LVEF) quantification, but as yet the prognostic value of LVEF assessment at any time after ST‐segment elevation myocardial infarction (STEMI) for subsequent major adverse cardiac event (MACE) prediction is uncertain. Purpose: To explore the prognostic impact of MRI‐derived LVEF at any time post‐STEMI to predict subsequent MACE (cardiovascular death or re‐admission for acute heart failure). Study Type: Prospective. Population: One thousand thirteen STEMI patients were included in a multicenter registry. Field Strength/Sequence: 1.5‐T. Balanced steady‐state free precession (cine imaging) and segmented inversion recovery steady‐state free precession (late gadolinium enhancement) sequences. Assessment: Post‐infarction MRI‐derived LVEF (reduced [r]: <40%; mid‐range [mr]: 40%–49%; preserved [p]: ≥50%) was sequentially quantified at 1 week and after >3 months of follow‐up. Statistical Tests: Multi‐state Markov model to determine the prognostic value of each LVEF state (r‐, mr‐ or p‐) at any time point assessed to predict subsequent MACE. A P ‐value <0.05 was considered to be statistically significant. Results: During a 6.2‐year median follow‐up, 105 MACE (10%) were registered. Transitions toward improved LVEF predominated and only r‐LVEF (at any time assessed) was significantly related to a higher incidence of subsequent MACE. The observed transitions from r‐LVEF, mr‐LVEF, and p‐LVEF states to MACE were: 15.3%, 6%, and 6.7%, respectively. Regarding the adjusted transition intensity ratios, patients in r‐LVEF state were 4.52‐fold more likely than those in mr‐LVEF state and 5.01‐fold more likely than those in p‐LVEF state to move to MACE state. Nevertheless, no significant differences were found in transitions from mr‐LVEF and p‐LVEF states to MACE state ( P ‐value = 0.6). Data Conclusion: LVEF is an important MRI index for simple and dynamic post‐STEMI risk stratification. Detection of r‐LVEF by MRI at any time during follow‐up identifies a subset of patients at high risk of subsequent events. Level of Evidence: 2 Technical Efficacy Stage: 2